(3eSGFd GdNdGa aj GdCUhd (B( (3Hjf GdHUQjjf hGdHZOGOjjf(B)s - (3CHh QTjO SYjO Hf eMeO Hf SYjO GdfjSGHhQjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje , GdMeO ddg hMOg eSCdI ai Cf Gddg JYGdi dGjLhR Cf jchf YGdekG s
(3BNQgG (B:s
(3aEPG CONd GdTQW ai ZjQ GdhLg GdPi bUOfGg , aPG eOM Hg ajeG ChQOfG HjGfg Je Pdc s
(3GdfSNI HgG MhGTs
(3HBNQgG ELGRIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds